Farmers’ reasoning behind the uptake of agroforestry practices: evidence from multiple case-studies across Europe - Rois-Díaz, Mercedes; Lovric, N.; Lovric, M.; Ferreiro-Domínguez, N.; Mosquera-Losada, María Rosa; den Herder, Michael; Graves, Anil; Palma, João H. N.; Paulo, J. A.; Pisanelli, Andrea; Smith, J.; Moreno, Gerardo; et al. (Springer, 2017)
Potential benefits and costs of agroforestry practices have been analysed by experts, but few studies have captured farmers’ perspectives on why agroforestry might be adopted on a European scale. This study provides answers to this question, through an analysis of 183 farmer interviews in 14 case study systems in eight European countries. The study systems included high natural and cultural value agroforestry systems, silvoarable systems, high value tree systems, and silvopasture systems, as well as systems where no agroforestry practices were occurring. A mixed method approach combining quantitative and qualitative approaches was taken throughout the interviews. Narrative thematic data analysis was performed. Data collection proceeded until no new themes emerged. Within a given case study, i.e. the different systems in different European regions, this sampling was performed both for farmers who practice agroforestry and farmers who did not. Results point to a great diversity of agroforestry practices, although many of the farmers are not aware of the term or concept of agroforestry, despite implementing the practice in their own farms. While only a few farmers mentioned eligibility for direct payments in the CAP as the main reason to remove trees from their land, to avoid the reduction of the funded area, the tradition in the family or the region, learning from others, and increasing the diversification of products play the most important role in adopting or not agroforestry systems.
Keywords: Interviews; Narrative thematic analysis; Driving forces; Farming